Women in the Shark Tank: Entrepreneurship and Feminism in a Neoliberal Age - Keren, Hila (Columbia Journal of Gender and Law, 2016)
Shark Tank is the American version of a reality television format featuring entrepreneurs pitching their business ideas in order to secure investment from a panel of venture capitalists. Every episode of the show consists of several pitches. In each pitch, an entrepreneur or a team of entrepreneurs (“pitchers”) presents an innovative business, seeking investment by one or more investors (“sharks”) out of a panel of ve, in exchange for equity in the presented business. All sharks are investing their own money, and successful pitches lead to deals that bring the entrepreneurs not only capital, but also the help of the investing shark(s) with business connections and mentorship. Currently on its seventh season, the show enjoys remarkable popularity. It has millions of viewers,2 and in both 2014 and 2015 it won the Emmy Award for Outstanding Structured Reality Program. Numerous avid fans who not only follow the show but also write about it in a variety of mediums, including social media, further enhance its impact.